Estudo de associação genômica e perfil de expressão gênica de folículos antrais em novilhas das raças nelore e angus, associadas ao fenótipo de alta e baixa população folicular - Favoreto, Maurício Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Animals with high antral follicle count (HFC) have a better reproductive performance when compared with animals with low follicle count (LFC). This variation in the number of antral follicles can be associated with different hormonal profiles and expression of genes regulating activation and follicular growth. The objective of the present work was: 1) to evaluate the global gene expression of antral follicles in animals with HFC and LFC in Nelore (Bos indicus) and Aberdeen Angus (Bos taurus) heifers and 2) to identify genotypic differences through a genomic wide association study (GWAS) using single nucleotide polymorphisms (SNP). Initially, 155 Nelore heifers and 132 Angus heifers with similar body weight and age were selected. The animals were synchronized and follicle count was done through ultrasound 24 to 48 h after estrus. The groups LFC and HFC were formed using the average of follicles ± standard deviation in both breeds. To evaluate the global gene expression profile we use a microarray chip. A total of 15 Nelore heifers (6 HFC and 9 LFC) and 17 Angus heifers (9 HFC and 8 LFC) were slaughter 12 to 24 h after ovulation and ovaries were transported to the laboratory. A pool of RNA from three follicles (< 4 mm) from each animal was used to the analysis using FlexArray 1.6.1.1 and the genes with fold change > 1.5 and P ≤ 0.05 were considered differentially expressed. For the GWAS study 72 Nelore heifers (32 HFC and 40 LFC) and 48 Angus heifers (21 HFC and 27 LFC) were selected. The DNA was extracted from blood and hair bulb and genotyping was done using the 777 HD Illumina chip. The SNPs were submitted to a quality control test using an exclusion criteria: call rate (IDCR) ≤ 90%, MAF ≤ 0.02, call rate (SNPCR) ≤ 0.98 and HWE ≤ 1 x 10-5. After the quality control test the SNPs were submitted to the Cochran-Armitage test to the association of phenotype/genotype in both breeds. The genes differentially expressed and the genes ...

Animais com alta população folicular (APF) antral possuem melhor desempenho reprodutivo quando comparados a animais de baixa população folicular (BPF). Essa variação no número de folículos antrais pode estar associada a diferentes perfis hormonais e de expressão de genes reguladores da ativação e crescimento folicular. Objetivou-se com o presente trabalho: 1) avaliar o perfil global de expressão gênica de folículos antrais em animais com APF e BPF nas raças Nelore (Bos indicus) e Aberdeen Angus (Bos taurus) e 2) identificar diferenças genotípicas através de um estudo de associação genômica (GWAS - Genome Wide Association Study) usando polimorfismos de nucleotídeo de sítio único (SNPs). Inicialmente foram avaliadas 155 novilhas da raça Nelore e 132 da raça Angus com idade e peso semelhantes. Os animais foram sincronizados e a contagem dos folículos realizada através de ultrassonografia 24 a 48 horas após o início do estro. Os grupos APF e BPF foram formados com base na média do número de folículos ± desvio padrão nas duas raças. Para avaliar o perfil global de expressão gênica usou-se a técnica do microarranjo. Um total de 15 novilhas Nelore (6 APF e 9 BPF) e 17 novilhas Angus (9 APF e 8 BPF) foram abatidas 12 a 24 horas após a ovulação e os ovários transportados ao laboratório. Foi realizado um pool de RNA extraído de três folículos (≤ 4 mm) individualmente (um pool por animal) dissecados do ovário. A análise dos dados procedeu-se no FlexArray 1.6.1.1 e os genes com fold change > 1,5 e P ≤ 0,05 foram considerados diferencialmente expressos. Para o estudo de GWAS 72 novilhas da raça Nelore (32 APF e 40 BPF) e 48 da raça Angus (21APF e 27 BPF) foram selecionadas. O DNA foi extraído do sangue e/ou bulbo capilar e a genotipagem foi realizada com o chip 777 HD bovine Illumina®. Os SNPs foram submetidos ao controle de qualidade usando como critérios de exclusão: call rate (IDCR) ≤ 90%,...
Genomic association and gene expression profile in antral follicles from nelore and angus heifers associated with the high and low follicle count phenotype
Keywords: Aberdeen-angus (Bovino); Bovino - Reprodução; Genômica; Expressão gênica; Nelore (Zebu); Genomics